2020
DOI: 10.7759/cureus.6603
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides Hyperinfection Presenting as a Gastric Outlet Obstruction

Abstract: Strongyloides is a unique nematode in its ability to cause a secondary hyperinfection and disseminated disease several years following initial contact. The prevalence of Strongyloides infection has been rising; it is currently considered a global disease, which presents with a broad spectrum of clinical signs and symptoms among patients. This case report focuses on a 67-year-old Caribbean female presenting with severe weight loss, vomiting, early satiety, and mild anemia who was subsequently diagnosed with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The case we described had gastric strongyloidiasis as part of his disseminated strongyloidiasis. Cases of disseminated strongyloidiasis with gastroduodenal involvement, including multiple granular lesions, ulcerations, and even duodenal obstruction, have been reported in the literature [ 9 , 10 ]. However, this is the first case of disseminated strongyloidiasis in which a patient presented with an ulcerated gastric mass and iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The case we described had gastric strongyloidiasis as part of his disseminated strongyloidiasis. Cases of disseminated strongyloidiasis with gastroduodenal involvement, including multiple granular lesions, ulcerations, and even duodenal obstruction, have been reported in the literature [ 9 , 10 ]. However, this is the first case of disseminated strongyloidiasis in which a patient presented with an ulcerated gastric mass and iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%
“…A negative stool result cannot exclude Strongyloidiasis because of the high false negative rate (up to 70% cases), probably due to the low parasite load and irregular larval output. 1,3,10 Multiple studies have suggested that obtaining 3-7 serial stool samples can significantly improve the diagnostic sensitivity from 50-99%. 1,3,10 On the other hand, the limitations of these tests include cross-reactions with other parasites and the prolonged persistence of antibodies even after treatment, making it difficult to distinguish between acute and chronic conditions based solely on the serum antibody levels.…”
Section: 4mentioning
confidence: 99%
“…1,3,10 Multiple studies have suggested that obtaining 3-7 serial stool samples can significantly improve the diagnostic sensitivity from 50-99%. 1,3,10 On the other hand, the limitations of these tests include cross-reactions with other parasites and the prolonged persistence of antibodies even after treatment, making it difficult to distinguish between acute and chronic conditions based solely on the serum antibody levels. 11 In this case, the patient tested positive for several parasites, which may be a cross-reaction or being infected by multiple endemic agents.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation